2009
DOI: 10.1111/j.1570-7458.2009.00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Differing acceptance of familiar and unfamiliar plant species by an oligophagous beetle

Abstract: The mustard leaf beetle, Phaedon cochleariae (F.) (Coleoptera: Chrysomelidae), is specialized to feed and develop on various species within the Brassicaceae. In this study, we investigated the acceptance of several host plant species (Brassica rapa L. and Sinapis alba L.), commonly used by the beetle (familiar plants), and of various unfamiliar plants, including systematically and chemically related [Bunias orientalis L. (Brassicaceae) and Tropaeolum majus L. (Tropaeolaceae), both Brassicales], as well as unre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Differences between sexes can also be demonstrated in response to olfactory cues. Odour in various Brassicaceae species including nonhost plants is reported to be highly effective in that P. cochleariae spend more time in air containing these volatiles in a four-chamber olfactometer than in clean control air, with females responding more strongly to odour than males (Kühnle & Müller, 2009). In the present study, both males and females respond to odour of N. officinale when tested in the stem arena, whereas only females show a preference for the main volatile compound 2-phenylethyl isothiocyanate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between sexes can also be demonstrated in response to olfactory cues. Odour in various Brassicaceae species including nonhost plants is reported to be highly effective in that P. cochleariae spend more time in air containing these volatiles in a four-chamber olfactometer than in clean control air, with females responding more strongly to odour than males (Kühnle & Müller, 2009). In the present study, both males and females respond to odour of N. officinale when tested in the stem arena, whereas only females show a preference for the main volatile compound 2-phenylethyl isothiocyanate.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the Brassicaceae contain glucosinolates as characteristic metabolites, which are readily hydrolysed to volatile isothiocyanates (Halkier & Gershenzon, 2006). Beetles of P. cochleariae show different preferences for different Brassicaceae species (Kühnle & Müller, 2009) and are partly stimulated by glucosinolates and their hydrolysis products (Tanton, 1977a; Reifenrath & Müller, 2008). Furthermore, the age of leaf tissue is an important determinant of host suitability for larval performance of this species (Reifenrath & Müller, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The plant has been present in non-native ecosystems for more than a century, but began a rapid expansion in the 1980s (Steinlein et al, 1996). Previous studies have shown that B. orientalis is of poor quality for the development of brassicaceous specialist herbivores from local populations in Germany and the Netherlands (Travers-Martin & M€ uller, 2008;K€ uhnle & M€ uller, 2009;Harvey et al, 2010a;Fortuna et al, 2012). By contrast, a Dutch population of a generalist herbivore, the cabbage moth Mamestra brassicae (Lepidoptera: Noctuidae), readily feeds on introduced populations of the plant and achieves high fitness on it (Harvey et al, 2010a;Harvey & Gols, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The other two chambers contained filter papers only. It has been demonstrated that insects are able to detect and respond to volatiles of different plant material under these circumstances (Kühnle & Müller, 2009). A gauze covering the cylinder served as the walking arena, on which a larva was placed in the centre.…”
Section: Test For Attraction To Volatile Cues Of Plant Partsmentioning
confidence: 99%